OPTIMALISASI AKURASI SMASH DAN DRIVE MELALUI DRILL GAWANG TARGET PADA ATLET BULUTANGKIS - Arfa Maulana Abrisam; Santika Rentika Hadi; Ismawandi Bripandika Putra; Eka Kurnia Darisman (Universitas Muhammadiyah Cirebon, 2026)
This study aimed to analyze the effect of target-gate-based training on improving the accuracy of Smash and drive strokes among badminton athletes of PB Surya Baja Surabaya. The study employed a quasi-experimental method using a one-group pretest–posttest design. The participants consisted of 20 badminton athletes, including 10 male and 10 female athletes, with a mean age of 17.00 ± 1.38 years. All participants completed a target-gate-based drill training program over 12 training sessions. The research instruments consisted of Smash and drive accuracy tests. Data were analyzed using descriptive statistics, normality testing, and a paired sample t-test. The results showed an increase in the mean scores across all variables after the intervention. The average accuracy scores for right and left Smashes improved from 17.95 and 17.20 to 28.20 and 27.75, respectively, while the average scores for right and left drives increased from 19.40 and 18.40 to 28.70 and 27.60. The paired sample t-test revealed significant differences between pretest and posttest scores across all variables (p < 0.05). Therefore, target-gate-based training was proven effective in improving the accuracy of Smash and drive strokes among PB Surya Baja Surabaya badminton athletes.